Beyond 1989 : re-reading German literary history since 1945 - Bullivant, Keith (Modern German studies (Providence, R.I.), 1997)
With the fall of the Berlin Wall in November 1989, four decades of separation seemed to have been brought to an end. In the literary arena as in many others, this seemed to be the surprising but ultimately logical end to the situation in which, after the extreme separation of the two Germanies' literatures during most of the period up to 1980, an increasing closeness could be observed during the 1980s, as relations between the two German states normalized.